PENGARUH KELEMBABAN, SUHU, ARAH DAN KECEPATAN ANGIN TERHADAP KONSENTRASI NITROGEN DIOKSIDA (NO2) DENGAN MEMBANDINGKAN 2 VOLUME SUMBER PENCEMAR DI AREA PABRIK DAN DI PERSIMPANGAN JALAN (Studi Kasus: PT. Inti General Yaja Steel dan Persimpangan Jrakah) - Giolding Hotma L (Jurnal Teknik Lingkungan, 2013)
The chimneys of the factory production process of steel and road transport activities can produce Nitrogen Dioxide (NO2) are dangerous. PT. Inti General Yaja Steel is a type of steel smelting industry uses MFO as fuel for their production activities and is located in front of the intersection whole observatories were crowded with vehicles. The volume of fuel used for burning MFO activity by PT. Inti General Yaja Steel core and the volume of vehicles passing through the intersection whole observatories are a source of Nitrogen Dioxide (NO2) which is spread in the air is affected by humidity, temperature, wind speed and direction. This study aimed to determine the effect of the volume of pollutant sources, humidity, temperature, wind direction and speed on the concentration of NO2 in the factory and at the intersection whole observatories. And to determine whether the concentration of NO2 mutually influenced by conditions in the two places. The study was conducted at a solid vehicle, while normal production factory and a factory is not producing. Based on these results, the concentration of NO2 in the area of plant range in value 17-32 μg/m3 and NO2 concentrations in the concentration range in values Highway 59-112 μg/m3 at a solid vehicle at normal production at the factory and non-factory production. NO2 concentrations at solid motor and car (9:00 to 10:00 a.m.), the concentration of NO2 in the normal production hours (15:00 to 16:00), and the non-production hours (7:00 p.m. to 20:00).The statistics show that there are significant differences in the concentrations of NO2 results in the area of the factory and at the intersection whole observatories. NO2 concentration in the plant area affected by the volume of fuel, humidity, temperature, wind speed and direction from the highway, while the concentration of NO2 in the intersection whole observatories affected by the volume of passing vehicles, humidity, temperature, wind speed and direction at the intersection whole observatories. NO2 concentration in the plant area affected by the volume of vehicles passing through, humidity, temperature, wind speed and direction at the intersection whole observatories, and vice versa, the concentration of NO2 in the intersection whole observatories affected by the volume of fuel, humidity, temperature, wind speed and direction in the area of plant .